PENGARUH GAYA KEPEMIMPINAN TERHADAP KINERJA PEGAWAI PADA KANTOR KECAMATAN SUNGKAI BARAT KABUPATEN LAMPUNG UTARA MELALUI MOTIVASI SEBAGAI VARIABEL MEDIASI - Erfina Berta Anggun Prasiska; Agung Rachmadi; Hengky Achmad Subing (Universitas Bandar Lampung (UBL), 2022)
This study aims to determine the effect of leadership style on employee performance through motivation as a mediating variableat the north sungkai subdistrict office north lampung, employees at the north sungkai sub district office in north lampung in carrying out prigram or tasks are always given direction by the leader and the pettern of relationship that are well estabilished between the leader.and subordinates so that enthusiasm to feel motivated so that they can achieve agency goals effectively and efficiently. The data used in this study is primary data, namely data obtained directly from the 35 respondets who filled out questionnaire and used econdry data, namely in the form of supporting data whose source in this study used path analysis with the help of the spss program. Based on the t-test, the spirit of the partial way of leadership style has a positive an significant effect on employee performance, the result of the f-test of leadership style and employee performace simultaneously have a positive and significant effect on motivation at the north Sungkai sub – district office north Lampung.